PENGARUH PELATIHAN DAN MOTIVASI KERJA GURU TERHADAP KINERJA GURU DI SD DAN SMP SWASTA BUDI MURNI 6 MEDAN - MAJU SIREGAR (JURNAL ILMIAH SIMANTEK, 2021)
Many factors that affect teacher performance include factors that affect teacher performance including teacher level, teachingsupervision, management program (training), conducive climate, facilities and infrastructure, physical and mental condition ofteachers, motivation, leadership style of the principal, welfare assurance, managerial ability of the principal and others.Teachers have a very complex function in the efforts to achieve goals, among which teachers serve as educators, teachersand mentors. Teacher performance is a teacher's ability to carry out learning tasks in school and is responsible for studentsunder his guidance by improving student learning achievement. Teacher performance in learning is the most important partin supporting the creation of an effective learning process. In an effort to improve teacher performance both in terms ofcompetence and skills in the learning process, schools need to pay attention to factors that can improve the teacher'sperformance in developing all their potential. One of them is by attending and Training (Training). However, there are stillsome low teacher performance, among others: teaching uncreatively in the sense of one-way learning without any learninginnovations, there are still teachers who are late in class and out of class before the scheduled change of lesson hours.